The contributions of livelihood resilience to reshaping adaptive capacity in rural China - Gu, Lei; Zhu, Qiantao; Zhao, Shanshan; Luo, Xinhong; Liu, Jiayi; Feldman, Marcus; Liu, Wei (Frontiers in Environmental Science, 2026)
More quantitative evidence is necessary on the link between livelihood resilience and livelihood adaptive capacity (LAC) in disaster resettlement. This study used 459 field research data collected from Ankang Prefecture, southern Shaanxi, China, examining how livelihood resilience influences adaptive capacity in the context of disaster-induced relocation. The resilience of rural household livelihood systems is described in terms of two components, general resilience, and specific resilience, which are quantified using the space vector method from systems engineering. The awareness, ability, and action framework is used to measure the LAC of rural households, and quantile regression is applied to explore the impact of livelihood resilience on LAC. Guided by the Sustainable Livelihoods Approach (SLA) and awareness, ability, action framework, we differentiate between cognitive, resource-based, and behavioral dimensions of adaptive capacity. The space vector method further reveals that individual adaptive capacity is reinforced by community-level resilience. It is found that: 1. livelihood resilience has a significant positive effect on high LAC levels, with the strongest effects observed at lower quantiles; as livelihood resilience increases, LAC also increases significantly. For rural households with low LAC levels, the impact is not significant; 2. general resilience and education have significant positive effects on all levels of LAC, with high levels being the most affected; 3. specific resilience has a significant negative effect on the lowest level of LAC only, and no significant effect on other levels. This study deepens our understanding of the relationship between livelihood resilience and LAC in the context of disaster resettlement, while testing the relationship between the two provides a methodological contribution to the study of disaster resettlement and community development.